Future-robust evolution of product portfolios: Need for action from theory and practice - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Interacting Forces for a Resilient, Future-robust Evolution of Product Portfolios - Wiederkehr, Ingrid; Schlegel, Michael; Koldewey, Christian; Rapp, Simon; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)

Guidelines for providing digital twins - Göllner, Denis; Dzienus, Sophie; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)

Mehr Innovationen durch Venture Clienting – Fallstudie zur Initiative „Stratosfare“ - Machon, Fabian; Haarmann, Lennard; Rabe, Martin; Dumitrescu, Roman; Bierbüsse, Marie; Tack, Mareen; Hanke, Rebecca; Kinder, Daniel (Vorausschau und Technologieplanung)

Bridging the Gap between Product Innovation and Product Planning: A literature-based Conceptual Investigation - Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman; Schlegel, Michael; Albers, Albert

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (Learning in the Age of Digital and Green Transition. ICL 2022. Lecture Notes in Networks and Systems)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Ontology for Future-robust Product Portfolio Evolution: A Basis for the Development of Models and Methods - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Towards a systematic approach for Prescriptive Analytics use cases in smart factories - Weller, Julian; Nico Migenda, Nico Migenda; Rui Liu, Rui Liu; Arthur Wegel, Arthur Wegel; Martin Kohlhase, Martin Kohlhase; Wolfram Schenck, Wolfram Schenck; Sebastian von Enzberg, Sebastian von Enzberg; Dumitrescu, Roman

Skill Sets for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (2023 IEEE AFRICON)

Should I Really do That? Using Quantile Regression to Examine the Impact of Sanctions on Information Security Policy Compliance Behavior - Hengstler, S.; Kuehnel, S.; Masuch, K.; Nastjuk, I.; Trang, Simon Thanh-Nam (Computers & Security)

A Topic Model for the Data Web - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs and Semantic Web)
Keywords: sail dice roeder kuchelev ngonga

Explainable Integration of Knowledge Graphs Using Large Language Models - Ahmed, Abdullah Fathi Ahmed; Firmansyah, Asep Fajar; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Linked knowledge graphs build the backbone of many data-driven applications such as search engines, conversational agents and e-commerce solutions. Declarative link discovery frameworks use complex link specifications to express the conditions under which a link between two resources can be deemed to exist. However, understanding such complex link specifications is a challenging task for non-expert users of link discovery frameworks. In this paper, we address this drawback by devising NMV-LS, a language model-based verbalization approach for translating complex link specifications into natural language. NMV-LS relies on the results of rule-based link specification verbalization to apply continuous training on T5, a large language model based on the Transformerarchitecture. We evaluated NMV-LS on English and German datasets using well-known machine translation metrics such as BLUE, METEOR, ChrF++ and TER. Our results suggest that our approach achieves a verbalization performance close to that of humans and outperforms state of the art approaches. Our source code and datasets are publicly available at https://github.com/dice-group/NMV-LS.

Unsupervised Relation Extraction with Sentence level Distributional Semantics - Manzoor, Ali; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (2023 IEEE 17th International Conference on Semantic Computing (ICSC))

Automating the Discovery of Linking Candidates - Röder, Michael
Keywords: dice roeder

Neural Class Expression Synthesis (Extended Abstract) - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (NeSy 2023, 17th International Workshop on Neural-Symbolic Learning and Reasoning, Certosa di Pontignano, Siena, Italy)
Keywords: 318 SFB-TRR demir dice enexa heindorf knowgraphs kouagou ngonga sail

Using Pre-trained Language Models for Abstractive DBPEDIA Summarization: A Comparative Study - Zahera, Hamada Mohamed Abdelsamee; Vitiugin, Fedor; Sherif, Mohamed; Castillo, Carlos; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: dice kiam ngonga porque sherif zahera

LauNuts: A Knowledge Graph to identify and compare geographic regions in the European Union - Wilke, Adrian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web (ESWC 2023))
Keywords: dice eml4u ngonga opal wilke

Native Execution of GraphQL Queries over RDF Graphs Using Multi-way Joins - Karalis, Nikolaos; Bigerl, Alexander; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS)
Keywords: bigerl dice enexa karalis knowgraphs ngonga sail

Parameterized Complexity of Logic-based Argumentation in Schaefer’s Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (ACM Transactions on Computational Logic)
Argumentation is a well-established formalism dealing with conflicting information by generating and comparing arguments. It has been playing a major role in AI for decades. In logic-based argumentation, we explore the internal structure of an argument. Informally, a set of formulas is the support for a given claim if it is consistent, subset-minimal, and implies the claim. In such a case, the pair of the support and the claim together is called an argument. In this article, we study the propositional variants of the following three computational tasks studied in argumentation: ARG (exists a support for a given claim with respect to a given set of formulas), ARG-Check (is a given set a support for a given claim), and ARG-Rel (similarly as ARG plus requiring an additionally given formula to be contained in the support). ARG-Check is complete for the complexity class DP, and the other two problems are known to be complete for the second level of the polynomial hierarchy (Creignou et al. 2014 and Parson et al., 2003) and, accordingly, are highly intractable. Analyzing the reason for this intractability, we perform a two-dimensional classification: First, we consider all possible propositional fragments of the problem within Schaefer’s framework (STOC 1978) and then study different parameterizations for each of the fragments. We identify a list of reasonable structural parameters (size of the claim, support, knowledge base) that are connected to the aforementioned decision problems. Eventually, we thoroughly draw a fine border of parameterized intractability for each of the problems showing where the problems are fixed-parameter tractable and when this exactly stops. Surprisingly, several cases are of very high intractability (para-NP and beyond).